Podwójne nazewnictwo na Śląsku Cieszyńskim (Zaolziu) od czasów monarchii habsburskiej po dzień dzisiejszy - Szymeczek, Józef (Górnośląskie Studia Socjologiczne. Seria Nowa, 2021)
The article presents the process of introduction of double naming to the Cieszyn lands, later to Zaolzie. It presents this process in the space of time from the middle of the 19th century to the present day. It devotes attention to the time of the Austro-Hungarian Empire, the interwar Czechoslovak Republic, post-war Czechoslovakia and the contemporary Czech Republic. In the context of dual naming, it draws attention to the legislative solutions of individual governments and to the use of dual naming in practice during specific periods. The article does not avoid describing sensitive issues such as the destruction of bilingual signs with double names of places and streets, or the growing wave of aversion towards Poles.